Correlated Study of Material Interaction Between Capillary Printed Eutectic Gallium Alloys and Gold Electrodes (Small 42/2022). Issue 42 (20th October 2022) - Hussain, Navid; Scherer, Torsten; Das, Chittaranjan; Heuer, Janis; Debastiani, Rafaela; Gumbsch, Peter; Aghassi‐Hagmann, Jasmin; Hirtz, Michael
Abstract : Liquid Metal Electronics In article number 2202987, Michael Hirtz and co‐workers take a close look at gold/liquid metal contacts as they appear, e.g., in flexible electronics. By correlating complementary chemical and morphological characterization techniques, new details on the evolution of such contacts are revealed.